Allometric Growth of Prenatal Organs as a Function of Age in the Japanese Quail Embryo, Coturnix japonica - Arora, Kashmiri L. (International Journal of Poultry Science, 2011)
The Japanese quail is widely being used as a model in developmental biology. Embryonic organs are sensitive indicators of pathological and treatment-induced alterations. There is a shortage of well characterized allometric information in the literature for assessing the prenatal growth in the Japanese quail. This study collected baseline information on the relative growth of various internal organs and external morphological structures during the prenatal life of the Japanese quail from day 10 to hatchling for use in comparative and pathological studies. The organs examined were the brain, eyes, liver, gizzard, proventriculus, heart, lungs and kidneys. This information would be potentially valuable to the scientific community for defining the processes involved in organogenesis, teratogenesis, comparison of growth among different age and genetic groups, physio-pathological responses to drugs, disease conditions and the evaluation of therapeutic drugs and environmental stresses.